2022
DOI: 10.1002/smll.202202663
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Hydrogel to Modulate T Cells for Cancer Immunotherapy

Abstract: T cell exhaustion caused by mitochondrial dysfunction is the major obstacle of T cells‐based cancer immunotherapy. Besides exhausted T cells, the insufficient major histocompatibility complex class I (MHC I) on tumor cells leads to inefficient T cell recognition of tumor cells, compromising therapeutic efficacy. Therapeutic platform to regulate T cell exhaustion and MHC I expression for boosting T cells‐based cancer immunotherapy has not been realized up to date. Herein, an injectable hydrogel is designed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The hydrogel can be loaded with multiple types of immune checkpoint blockers and chemicals that can increase cancer immunogenicity and enhance cytotoxic T lymphocyte infiltration. The hydrogel also allows for the sustained release of these drugs in a sequence that not only induces a cascade of immune responses for synergistic therapeutic benefits, but also reduces drug resistance and the number of injections ( Zhang et al, 2022a ; Passaro et al, 2022 ). In addition, the encapsulation of the hydrogel enhances the penetration of immunotherapeutic agents to a certain extent and facilitates the long-term accumulation of drugs ( Li et al, 2021 ).…”
Section: Hydrogels Can Be Used In Multiple Treatments For Cancermentioning
confidence: 99%
“…The hydrogel can be loaded with multiple types of immune checkpoint blockers and chemicals that can increase cancer immunogenicity and enhance cytotoxic T lymphocyte infiltration. The hydrogel also allows for the sustained release of these drugs in a sequence that not only induces a cascade of immune responses for synergistic therapeutic benefits, but also reduces drug resistance and the number of injections ( Zhang et al, 2022a ; Passaro et al, 2022 ). In addition, the encapsulation of the hydrogel enhances the penetration of immunotherapeutic agents to a certain extent and facilitates the long-term accumulation of drugs ( Li et al, 2021 ).…”
Section: Hydrogels Can Be Used In Multiple Treatments For Cancermentioning
confidence: 99%
“…[43,44] As peripheral blood mononuclear cell (PBMCs) have been reported to reflect the behaviors of tumorinfiltrating T cells, [45] they were used as surrogates for T cells in in vitro studies. [46] We assessed the influence of CQ-NCPmediated PD-L1 downregulation on T cell function by apoptosis assays of CQ-NCP-treated MC38 cells with or without co-incubation of PBMCs (Figure 3c,d). CQ-NCP treatment only caused 3.57 ± 0.57% cell death, but the addition of PBMCs significantly increased the apoptosis percentage to 22.35 ± 2.97%, suggesting that CQ-NCP enhanced the activity of PBMCs via PD-L1 downregulation.…”
Section: Ox/gc/cq Enhances Activity Of Pbmcsmentioning
confidence: 99%
“…Indeed, axitinib helped supply oxygen into the TME for recovery of mitochondrial function. [84] Reactive oxygen species (ROS) are known to cause aging or cancer in normal tissues, and interestingly also increase in hypoxia. [121] Although ROS has beneficial properties such as polarization of macrophages to pro-inflammatory phenotype, it has dual effects [135] in turning tumor microenvironments to be more immunosuppressive.…”
Section: The Chemical Barriermentioning
confidence: 99%
“…[154] As mentioned previously, Zhang et al encapsulated multiple chemotherapeutic drugs in nanoparticles within O-TMV, such as 4-1BB antibody, a T cell activating agent, and PCSK9 inhibitor, an anti-cancer drug, to enhance T cell viability and reversion from exhaustion. [84] In vitro and in vivo experiments revealed that the hydrogel scaffold effectively reversed T cell exhaustion through promotion of mitochondrial biogenesis through alleviated hypoxia and increased T cell proliferation, and triggered improved recognition of cancer cells by T cells. This study is especially valuable as the immunosuppressive TME can easily exhaust T cells that make it to the tumor site, and rejuvenation of T cells in tumor tissues is especially important in solid tumors for successful therapy.…”
Section: The Metabolic Barriermentioning
confidence: 99%